2020
DOI: 10.3390/app11010006
|View full text |Cite
|
Sign up to set email alerts
|

Why Farmers Get Involved in Participatory Research Projects? The Case of Arable Crops Farmers in Greece

Abstract: This paper seeks to underline the driving factors of farmers’ engagement in Participatory Research Projects (PRPs). This is a critical issue for formulating efficient and effective technology transfer channels, essential for improving the operational status of agricultural holdings. A survey was conducted on a sample of 326 Greek arable crops farmers. An explanatory framework consisting of three major factor categories and 11 variables was developed. A logistic regression analysis empirically tests the effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…However, we often note the absence of a real analysis of the concrete actions carried out following these participatory foresight processes in agriculture, of their scope, of the actors involved, but also of the possible discrepancy existing with participatory discussions and actions taken afterwards. While some studies have addressed the reason of farmers to get involved in participatory research projects, few have attempted comparable studies/researches on the question of real actions a posteriori (Vlontzos et al, 2021). It's particularly true with farmers although they play a key role as the primary operator that acts on the territory (Menconi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, we often note the absence of a real analysis of the concrete actions carried out following these participatory foresight processes in agriculture, of their scope, of the actors involved, but also of the possible discrepancy existing with participatory discussions and actions taken afterwards. While some studies have addressed the reason of farmers to get involved in participatory research projects, few have attempted comparable studies/researches on the question of real actions a posteriori (Vlontzos et al, 2021). It's particularly true with farmers although they play a key role as the primary operator that acts on the territory (Menconi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Our study indicated that participants expressed a need for educational resources such as hands-on learning opportunities and a hybrid part in-class part on-farm training option in our study. Participatory teaching and learning strategies have been suggested as effective agricultural education methods (Franz et al, 2010;Vlontzos et al 2020). Making growers more aware of the appropriate educational resources that have already been developed and ensuring that they are readily accessible can also aid in facilitating the food safety information needs gaps of growers (Rodrigues et al, 2020).…”
Section: Discussionmentioning
confidence: 99%